Die schriftbildliche Gestaltung von lexikalisch übernommenen Markennamen. Ein explorativer Wahrnehmungstest zum graduellen Entrenchment von Markennamen als multimodale Konstruktionen - Dübbert, Alexander (Beiträge zur Namenforschung)
Dieser Beitrag untersucht, inwiefern sich die kognitive Verankerung von der schriftbildlichen Gestaltung lexikalisch übernommener Markennamen nachweisen lässt. Dazu werden die Ergebnisse eines tachistoskopischen Wahrnehmungstests ausgewertet, bei dem einer Testgruppe die Schriftbilder (Logos) der Markennamen 'FÜR', 'Landliebe', 'MONSTER', 'GUT & GÜNSTIG', 'kinder' und 'ja!' mehrmals für Sekundenbruchteile (0,01s, 0,02s, 0,1s und 1,0s) und teils mit substituiertem Schriftzug präsentiert wurden. Insgesamt deutet die explorative Untersuchung – mit graduellen Abweichungen – in die Richtung, dass die Wahrnehmung des Schriftbilds zum Erkennen des dazugehörigen Markennamens führt. Dies ermöglicht die Schlussfolgerung, dass sich die getesteten Markennamen als multimodale Konstruktionen mit konstitutiver Schriftbildlichkeit qualifizieren.

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Open Research Practices and Cultural Change: A Commentary on “(Why) Are Open Research Practices the Future for the Study of Language Learning?” - Steinhardt, Isabel; Mauermeister, Sylvi; Schmidt, Rebecca (Language Learning)
Keywords: Open Science; Open Science Practices; Cultural Change

Teacher's roles and teacher professionalism - Lin-Januszewski, Liang-Wen (Sociology of education: Theory, experience and implication)

The Bot Delusion. ChatGPT and anticipated consequences for research communication - Wieczorek, Oliver; Steinhardt, Isabel; Schneijderberg, Christian; Schmidt, Rebecca; Mauermeister, Sylvi
The reproduction of social inequalities through artificial intelligence (AI) and machine learning via artificial neural networks (ANN) has been demonstrated empirically in various areas of society, for instance in policing and personnel hiring decisions. Yet, a broader discussion is missing to what extent ANN technological developments may affect the scientific enterprise and reinforce or mitigate existing structural inequalities in academia. Focusing on publications and citations as main currencies in science, the anticipated consequences of ChatGPT on the research communication of existing and new knowledges are discussed in three scenarios, which echo the social structures in academia.

Die Rechtfertigung des Kapitalismus und die Kritik. Der neue Geist des Kapitalismus von Luc Boltanski und Ève Chiapello - Knoll, Lisa (Soziologische Gegenwartsdiagnosen 3)

Similar Affordances, Different Use Practices? An Investigation of Socio-Cultural Contexts in Facebook, Instagram and Twitter - Arslan, Kader; Trier, Matthias (Proceedings of the 44th International Conference on Information Systems (ICIS 2023))

Discrete Lagrangian Neural Networks with Automatic Symmetry Discovery - Lishkova, Yana; Scherer, Paul; Ridderbusch, Steffen; Jamnik, Mateja; Liò, Pietro; Ober-Blöbaum, Sina; Offen, Christian (IFAC-PapersOnLine)
By one of the most fundamental principles in physics, a dynamical system will exhibit those motions which extremise an action functional. This leads to the formation of the Euler-Lagrange equations, which serve as a model of how the system will behave in time. If the dynamics exhibit additional symmetries, then the motion fulfils additional conservation laws, such as conservation of energy (time invariance), momentum (translation invariance), or angular momentum (rotational invariance). To learn a system representation, one could learn the discrete Euler-Lagrange equations, or alternatively, learn the discrete Lagrangian function Ld which defines them. Based on ideas from Lie group theory, in this work we introduce a framework to learn a discrete Lagrangian along with its symmetry group from discrete observations of motions and, therefore, identify conserved quantities. The learning process does not restrict the form of the Lagrangian, does not require velocity or momentum observations or predictions and incorporates a cost term which safeguards against unwanted solutions and against potential numerical issues in forward simulations. The learnt discrete quantities are related to their continuous analogues using variational backward error analysis and numerical results demonstrate the improvement such models can have both qualitatively and quantitatively even in the presence of noise.

Ernst Schröder’s Algebra of Logic and the ‘Logic of the Ancient - Peckhaus, Volker (Aristotle’s Syllogism and the Creation of Modern Logic: Between Tradition and Innovation, 1820s–1930s (Bloomsbury Studies in the Aristotelian Tradition))

Nakano, Anderson: On Ramsey’s Reason to Amend Principia Mathematica’s Logicism and Wittgenstein’s Reaction, Synthese 199 (2021), 2629–2646. - Peckhaus, Volker (Mathematical Reviews MR4341825)

Schappacher, Norbert. Framing Global Mathematics. The International Mathematical Union between Theorems and Politics, Springer: Cham 2022 - Peckhaus, Volker (Mathematical Reviews MR4461006)

Aranda, Victor. Completeness: From Husserl to Carnap. Logica Universalis 16 (2022), 57–83 - Peckhaus, Volker (Mathematical Reviews MR4451488)

Floyd, Juliet und Felix Mühlhölzer, Wittgenstein’s Annotations to Hardy’s Course of Pure Mathematics. An Investigation of Wittgenstein’s Non-Extensionalist Understanding of the Real Numbers, Springer: Cham 2020 (Nordic Wittgenstein Studies, 7). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07214204)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 6: Taschennotizbücher1931–32. Anmerkungen, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2022, xiii, 192 S. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07469681)

Hogan, Desmond, “Kant and the Character of Mathematical Inference”, in: Carl Posy et al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 126–154 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1570.01020)

Schlimm, Dirk, "Pasch’s Empiricism as Methodological Structuralism." In: Erich H. Reck und Georg Schiemer (eds.), The Prehistory of Mathematical Structuralism, Oxford: University Press 2020, 88–105 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.01017)

Bellomo, Anna und Guillaume Massas, Bolzano’s Mathematical Infinite. The Review of Symbolic Logic 16, No. 1 (2023), 59–113 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1515.01010)

Tschirk, Wolfgang, Vom Universum des Denkens. Eine Geistesgeschichte der Logik, Springer: Berlin 2022 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.03007)

Herrmann, Kay (Hg.), Grete Henry-Hermann: Philosophie – Mathematik – Quantenmechanik. Texte zur Naturphilosophie und Erkenntnistheorie, mathematisch-physikalische Beiträge sowie ausgewählte Korrespondenz aus den Jahren 1925 bis 1982. Springer VS: Wiesbaden 2019, xv + 664 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1506.01002)

SIG: Adaptivität und Adaptive Lehrkompetenz grundschulpädagogisch und (fach-)didaktisch reloaded - Reh, Anne; Schroeder, René; Miller, Susanne; Blumberg, Eva; Kottmann, Brigitte; Thevißen, Max

On the Dynamical Hierarchy in Gathering Protocols with Circulant Topologies - Gerlach, Raphael; von der Gracht, Sören; Dellnitz, Michael (arXiv:2305.06632)
In this article we investigate the convergence behavior of gathering protocols with fixed circulant topologies using tools form dynamical systems. Given a fixed number of mobile entities moving in the Euclidean plane, we model a gathering protocol as a system of ordinary differential equations whose equilibria are exactly all possible gathering points. Then, we find necessary and sufficient conditions for the structure of the underlying interaction graph such that the protocol is stable and converging, i.e., gathering, in the distributive computing sense by using tools from dynamical systems. Moreover, these tools allow for a more fine grained analysis in terms of speed of convergence in the dynamical systems sense. In fact, we derive a decomposition of the state space into stable invariant subspaces with different convergence rates. In particular, this decomposition is identical for every (linear) circulant gathering protocol, whereas only the convergence rates depend on the weights in interaction graph itself.
Keywords: Dynamical Systems; Coupled Systems; Distributed Computing; Robot Swarms; Autonomous Mobile Robots; Gathering

Politisierung von Jugend – Zur Einführung in den Band - Dahmen, Stephan; Demir, Zeynep; Ertugul, Baris; Kloss, Daniela; Ritter, Bettina (Politisierung der Jugend)

Politisierung von Jugend

Empirische Zugänge zu organisational kontextualisierter Professionalität - Dahmen, Stephan; Henn, Sarah; Ritter, Bettina; Mohr, Simon (Sozialpädagogische Professionalisierung in der Krise?)

Hydrodynamic and Non-hydrodynamic Excitations in Kinetic Theory -- A Numerical Analysis in Scalar Field Theory - Ochsenfeld, Stephan; Schlichting, Sören (arXiv:2308.04491)
Viscous hydrodynamics serves as a successful mesoscopic description of the Quark-Gluon Plasma produced in relativistic heavy-ion collisions. In order to investigate, how such an effective description emerges from the underlying microscopic dynamics we calculate the hydrodynamic and non-hydrodynamic modes of linear response in the sound channel from a first-principle calculation in kinetic theory. We do this with a new approach wherein we discretize the collision kernel to directly calculate eigenvalues and eigenmodes of the evolution operator. This allows us to study the Green's functions at any point in the complex frequency space. Our study focuses on scalar theory with quartic interaction and we find that the analytic structure of Green's functions in the complex plane is far more complicated than just poles or cuts which is a first step towards an equivalent study in QCD kinetic theory.

Wo lässt es sich im Universum leben? Eine Reise zu großen Sternen und kleinen Planeten - Hohmann, Sascha (Außerirdisches Leben)
Fast 5.000 Planeten in anderen Sternensystemen wurden inzwischen detektiert. Aber ist die Erde der einzige Planet, auf dem Leben möglich wäre? Kommt es dabei nur auf flüssiges Wasser und damit die Temperatur auf dem Planeten an oder gibt es noch andere Bedingungen, die Planet und Stern erfüllen müssen? Und warum sind die meisten bisher gefundenen Planeten dafür ziemlich ungeeignet? Diese und weitere Fragen sollen hier beantwortet werden.

Untersuchung des Einflusses von Relativverschiebungen während der Aushärtung auf die mechanischen Eigenschaften von Klebverbindungen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Himmelskörper mit Geometrie - Hohmann, Sascha (Der Mathematikunterricht)

Experimentelle Untersuchung des Ermüdungsverhaltens von strukturellen Klebverbindungen und Berechnung der Lebensdauer unter Berücksichtigung der Spannungsanisotropie - Tews, Karina; Çavdar, Serkan; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien
Der vorliegende Band versammelt intersektionale literaturwissenschaftliche und -didaktische Fallstudien aus unterschiedlichen Philologien und bietet so ein Prisma der Erforschung literarischer Repräsentationen des Zusammenspiels von einander verschärfenden bzw. abschwächenden Diskriminierungskategorien. Die Einzelbeiträge präsentieren kritische Reflexionen und Modifizierungen verschiedener Positionen der intersektionalen Forschung sowie Beispiele für die vielfältige Ausgestaltung intersektional orientierter Textanalyse auf theoretischer und methodischer Ebene. Da wissenschaftliche und literarische ebenso wie zeitgenössische und historische Texte in verschiedenen Sprachen (Englisch, Deutsch, Italienisch, Niederländisch, Spanisch etc.) aufgegriffen werden, zeigt der Band auf, dass Machtstrukturen in unterschiedlichen kulturellen Kontexten Analogien aufweisen, deren Analyse von Differenzierungen verschiedener Herrschaftsstrukturen profitiert.
Keywords: Intersektionalität; Literaturwissenschaft; Literaturunterricht; Klassenlektüre; Auswahl; Textanalyse; Literatur; Erzähltheorie; Machtstruktur; Diskriminierung; Geschlechterrolle; Geschlechterverhältnis; Geschlechtsidentität; Rassismus; Soziale Klasse; Othering; Feminismus

Serielles Erzählen kolonialer Rhetoriken. Ein diskursreflexives Unterrichtsmodell an der Schnittstelle von literaturunterrichtlichem und literaturmusealem Lernen - Kißling, Magdalena (Diversität und Darstellung. Zugehörigkeit und Ausgrenzung im Literaturmuseum und in den Literaturwissenschaften)

Memory Gym: Towards Endless Tasks to Benchmark Memory Capabilities of Agents - Pleines, Marco; Pallasch, Matthias; Zimmer, Frank; Preuss, Mike (arXiv:2309.17207)
Memory Gym presents a suite of 2D partially observable environments, namely Mortar Mayhem, Mystery Path, and Searing Spotlights, designed to benchmark memory capabilities in decision-making agents. These environments, originally with finite tasks, are expanded into innovative, endless formats, mirroring the escalating challenges of cumulative memory games such as ``I packed my bag''. This progression in task design shifts the focus from merely assessing sample efficiency to also probing the levels of memory effectiveness in dynamic, prolonged scenarios. To address the gap in available memory-based Deep Reinforcement Learning baselines, we introduce an implementation that integrates Transformer-XL (TrXL) with Proximal Policy Optimization. This approach utilizes TrXL as a form of episodic memory, employing a sliding window technique. Our comparative study between the Gated Recurrent Unit (GRU) and TrXL reveals varied performances across different settings. TrXL, on the finite environments, demonstrates superior sample efficiency in Mystery Path and outperforms in Mortar Mayhem. However, GRU is more efficient on Searing Spotlights. Most notably, in all endless tasks, GRU makes a remarkable resurgence, consistently outperforming TrXL by significant margins. Website and Source Code: https://github.com/MarcoMeter/endless-memory-gym/

Wahrnehmen von Missverhältnissen. Inkongruenzkomik in Fernsehserien zur Förderung literarischen Lernens - Kißling, Magdalena (Was gibt es da noch zu lachen? Komik in Texten und Medien der Gegenwartskultur in litera-turdidaktischer Perspektive)

Game of Thrones: (Re)arrangend gender roles on screen? - Eremin, Oxana (Bulletin-Texte 47, GenderErträgeV. Texts from the SVR Student Lecture Series)

Towards active learning: A stopping criterion for the sequential sampling of grain boundary degrees of freedom - Schmalofski, Timo; Kroll, Martin; Dette, Holger; Janisch, Rebecca (arXiv:2302.01603)
Many materials processes and properties depend on the anisotropy of the energy of grain boundaries, i.e.~on the fact that this energy is a function of the five geometric degrees of freedom (DOF) of the interface. To access this parameter space in an efficient way and to discover energy cusps in unexplored regions, a method was recently established, which combines atomistic simulations with statistical methods 10.1002/adts.202100615. This sequential sampling technique is now extended in the spirit of an active learning algorithm by adding a criterion to decide when the sampling has advanced enough to stop. In this instance, two parameters to analyse the sampling results on the fly are introduced: the number of cusps, which correspond to the most interesting and important regions of the energy landscape, and the maximum change of energy between two sequential iterations. Monitoring these two quantities provides valuable insight into how the subspaces are energetically structured. The combination of both parameters provides the necessary information to evaluate the sampling of the 2D subspaces of grain boundary plane inclinations of even non-periodic, low angle grain boundaries. With a reasonable number of data points in the initial design, only a few appropriately chosen sequential iterations already improve the accuracy of the sampling substantially and unknown cusps can be found within a few additional sequential steps.

Pre-Equilibrium Evolution of Conserved Charges with ICCING Initial Conditions - Carzon, Patrick; Martinez, Mauricio; Jacquelyn Noronha-Hostler, Jacquelyn Noronha-Hostler; Plaschke, Philip; Schlichting, Soeren; Sievert, Matthew (arXiv:2301.04572)
Heavy-ion collisions can be well described through relativistic viscous hydrodynamics, but questions still remain when hydrodynamics is applicable because the initial state may begin very far-from-equilibrium. Thus, a pre-equilibrium evolution phase is used to bridge the gap between the initial state and hydrodynamics. K$φ$MP$φ$ST is one such pre-equilibrium model that propagates the energy-momentum tensor by decomposing it into the background and fluctuations around that background, whose evolution is captured by Green's functions. We extend this formalism to include conserved charges and calculate the corresponding non-equilibrium Green's functions in the relaxation time approximation. The ICCING algorithm initializes conserved charges in the initial state by sampling $g → q\bar{q}$ splitting probabilities and is, thus, perfectly positioned to implement Green's functions for charge propagation. We show that this method alters the initial state charge geometries and is applicable in central to mid-central collisions.

Implications of Algorithmic Wage Setting on Online Labor Platforms: a Simulation-Based Analysis∗ - Dawid, Herbert; Harting, Philipp; Neugart, Michael (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Universality of energy-momentum response in kinetic theories - Du, Xiaojian; Ochsenfeld, Stephan; Schlichting, Sören (arXiv:2306.09094)
We study the response of the energy-momentum tensor in several kinetic theories, from the simple relaxation time approximation (RTA) to Quantum Chromodynamics (QCD). Irrespective of the differences in microscopic properties, we find a remarkable degree of universality in the response functions from conformal theories. We find that the response to scalar perturbations in kinetic theory can be effectively described by a pair of one hydrodynamic sound mode and one non-hydrodynamic mode. We find that even beyond the range of validity of hydrodynamics, the energy-momentum response in position space can be effectively described by one single mode with non-trivial dispersion relation and residue.

Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad - Bauer, Matthias (Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad)

Optogenetics reveals paradoxical network stabilizations in hippocampal CA1 and CA3 - de Jong, Laurel Watkins; Nejad, Mohammadreza Mohagheghi; Yoon, Euisik; Cheng, Sen; Diba, Kamran (Current Biology)

Investigation of the Compatibility between Warheads and Peptidomimetic Sequences of Protease Inhibitors—A Comprehensive Reactivity and Selectivity Study - Müller, Patrick; Meta, Mergim; Meidner, Jan Laurenz; Schwickert, Marvin; Meyr, Jessica; Schwickert, Kevin; Kersten, Christian; Zimmer, Collin; Hammerschmidt, Stefan Josef; Frey, Ariane; Lahu, Albin; de la Hoz-Rodríguez, Sergio; et al. (International Journal of Molecular Sciences)
Covalent peptidomimetic protease inhibitors have gained a lot of attention in drug development in recent years. They are designed to covalently bind the catalytically active amino acids through electrophilic groups called warheads. Covalent inhibition has an advantage in terms of pharmacodynamic properties but can also bear toxicity risks due to non-selective off-target protein binding. Therefore, the right combination of a reactive warhead with a well-suited peptidomimetic sequence is of great importance. Herein, the selectivities of well-known warheads combined with peptidomimetic sequences suited for five different proteases were investigated, highlighting the impact of both structure parts (warhead and peptidomimetic sequence) for affinity and selectivity. Molecular docking gave insights into the predicted binding modes of the inhibitors inside the binding pockets of the different enzymes. Moreover, the warheads were investigated by NMR and LC-MS reactivity assays against serine/threonine and cysteine nucleophile models, as well as by quantum mechanics simulations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Apologie für das Nebensächliche. Prinzipien einer intersektional orientierten Unterrichtsmodel-lierung am Beispiel von Aneignungsperspektiven zu einer jugendpopulären Fernsehserie - Kißling, Magdalena (Rassismussensibler Literaturunterricht – Grundlagen, Dimensionen, Herausforderungen, Möglichkeiten)

Differenzkonstruktionen in Explikation und Beiläufigkeit. Vergleichende Betrachtungen zur Wirkungsästhetik bei Fünftklässler:innen hinsichtlich unterschiedlichen kinderliterarischen Erzählens von Diversität - Kißling, Magdalena ("So viel Größenwahn muss sein!" Kinderliteratur - Schule - Gesellschaft)

Diskriminierungssensible Methoden. Neue Lernwege im kulturwissenschaftlich ausgerichteten Literaturunterricht - Kißling, Magdalena (Neue Perspektiven einer kulturwissenschaftlich orientierten Literaturdidaktik)

Hannah Arendt and Politics - Robaszkiewicz, Maria Anna; Weinman, Michael D.

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Le Gall, François (SIAM Journal on Computing)
Keywords: General Mathematics; General Computer Science

Untersuchung der Dichtheitseigenschaften hybridgefügter Mischbauverbindungen für den Einsatz in Batterieghäusen für Elektrofahrzeuge - Schmolke, Tobias; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Experimentelle Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

Effizientes Lösen von Klebverbindungen in der Fahrzeuginstandsetzung - Chudalla, Nick; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)